Temporal trends in atrial fibrillation ablation procedures at an academic medical center: 2011−2021. (14th February 2023) - Kushnir, Alexander; Barbhaiya, Chirag R.; Aizer, Anthony; Jankelson, Lior; Holmes, Douglas; Knotts, Robert; Park, David; Spinelli, Michael; Bernstein, Scott; Chinitz, Larry A.
Abstract: Introduction: Radiofrequency ablation technology for treating atrial fibrillation (AF) has evolved rapidly over the past decade. We investigated the impact of technological and procedural advances on procedure times and ablation outcomes at a major academic medical center over a 10‐year period. Methods: Clinical data was collected from patients who presented to NYU Langone Health between 2011 and 2021 for a first‐time AF ablation. Time to redo AF ablation or direct current cardioversion (DCCV) for recurrent AF during a 3‐year follow‐up period was determined and correlated with ablation technology and practices, antiarrhythmic medications, and patient comorbid conditions. Results: From 2011 to 2021, the cardiac electrophysiology lab adopted irrigated‐contact force ablation catheters, high‐power short duration ablation lesions, steady‐pacing, jet ventilation, and eliminated stepwise linear ablation for AF ablation. During this time the number of first time AF ablations increased from 403 to 1074, the percentage of patients requiring repeat AF‐related intervention within 3‐years of the index procedure dropped from 22% to 14%, mean procedure time decreased from 271 ± 65 to 135 ± 36 min, and mean annual major adverse event rate remained constant at 1.1 ± 0.5%. Patient comorbid conditions increased during this time period and antiarrhythmic use was unchanged. Conclusion: Rates of redo‐AF ablation or DCCV following an initial AF ablation at a single center decreased 36% over a 10‐year period. Procedural and technological changes likely contributed to this improvement, despite increased AF related comorbidities.